Efficacy of arthrocentesis with injection of hyaluronic acid in the treatment of internal derangement of temporomandibular joint - Adil Al Kayat; Thair Abdul Lateef; Enas A Abdulmajed (College of Dentistry/ University of Baghdad, 2015)
Background: Temporomandibular joint disorders refer to a group of heterogeneous pain and dysfunction conditions involving the masticatory system, reducing life quality of the sufferers. Arthrocentesis is simple and less invasive surgical procedure for the treatment of internal derangement than arthroscopy and better than other conservative procedures such as drugs, occlusal appliances and physiotherapy. The aim of the study was to evaluate the effect of arthrocentesis with injection of hyaluronic acid in the treatment of internal derangement of temporomandibular joint for the restoration of its function, reducing pain and preventing further deterioration of the temporomandibular joint dysfunction. Materials and methods: This study was performed in Al-Sheed Ghazi Al-Hariri Hospital, Department of Oral and Maxillofacial Surgery, from November 2012 to October 2013, included 60 patients, aged 18 to 45 years with symptoms of temporomandibular joint pain, clicking during function and limited mouth opening. Temporomandibular joint internal derangement was assessed with clinical examination and confirmed with computed tomography scan. Arthrocentesis was done with insertion of two 18 gauge needles in the upper joint compartment, lavaged with ringer's lactate solution and at the end of the procedure 1ml of hyaluronic acid was injected. Intensity of temporomandibular joint pain was assessed using visual analog scale, maximum mouth opening was assessed with ruler scale and joint clicking was assessed clinically by stethoscope and manual palpation. All the parameters were measured before the procedure then 1 and 3 months later. Results: During 4 months follow-up, clinical examination and comparison of the results showed reduction in pain with success rate 95%, improvement in mouth opening with success rate 100% and clicking disappeared in 95% of patients. Conclusion: The technique of arthrocentesis using Sodium Hyaluronate injection, used in patients who presented with internal derangement, showed therapeutic benefits, simplicity, safety, patients acceptance of the technique and lack of significant side effects and complications.